2014
DOI: 10.1037/a0037714
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses and p-curves support robust cycle shifts in women’s mate preferences: Reply to Wood and Carden (2014) and Harris, Pashler, and Mickes (2014).

Abstract: Two meta-analyses evaluated shifts across the ovulatory cycle in women's mate preferences but reported very different findings. In this journal, we reported robust evidence for the pattern of cycle shifts predicted by the ovulatory shift hypothesis (Gildersleeve, Haselton, & Fales, 2014). However, Wood, Kressel, Joshi, and Louie (2014) claimed an absence of compelling support for this hypothesis and asserted that the few significant cycle shifts they observed were false positives resulting from publication bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 65 publications
(141 reference statements)
0
69
0
1
Order By: Relevance
“…The second meta-analysis by Gildersleeve et al (2014a) reported significant effects of higher fertility on masculinity preferences when women considered short-term relationships and attractiveness ratings for unspecified relationship contexts, but not when considering long-term relationships. However, subsequent reanalyses of the data included in both meta-analyses were mixed (Gildersleeve et al, 2014b;Wood & Fig. 4 Mean proportion of hairy images (±1 SEM) selected as most attractive for very light, light, medium, and heavy chest hair for the full sample (a) and among women 30 years or younger (b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second meta-analysis by Gildersleeve et al (2014a) reported significant effects of higher fertility on masculinity preferences when women considered short-term relationships and attractiveness ratings for unspecified relationship contexts, but not when considering long-term relationships. However, subsequent reanalyses of the data included in both meta-analyses were mixed (Gildersleeve et al, 2014b;Wood & Fig. 4 Mean proportion of hairy images (±1 SEM) selected as most attractive for very light, light, medium, and heavy chest hair for the full sample (a) and among women 30 years or younger (b).…”
Section: Discussionmentioning
confidence: 99%
“…We recognize that the use of questionnaires to determine fertility and likelihood of conception is imperfect (Harris, 2013;Harris, Chabot, & Mickes, 2013). In order to provide the best estimate of fertility in the absence of endocrine measures, accounting for length and regularity of the menstrual cycle has been recommended (Gildersleeve et al, 2013(Gildersleeve et al, , 2014b. Thus, among participants not using hormonal contraceptives, we restricted analyses to those participants reporting regular menstrual cycles to control for potential intra-cycle variability in the onset of theperiod of fertility (Wilcox et al, 2000).…”
Section: Ratersmentioning
confidence: 99%
“…Gildersleeve et al (2014a), meta-analyzing the same domain, reported highly robust effects (though also gaps in understanding). Differences that drive contrasting conclusions are multiple (see Gildersleeve, Haselton, & Fales, 2014b), but are not the focus here. Wood et al (2014) found certain groups of cycle effects to be robustspecifically, on preferences for symmetry and health, the effect for masculinity preferences just falling short of significance (see also Gildersleeve et al, 2014aGildersleeve et al, , 2014b.…”
mentioning
confidence: 99%
“…Differences that drive contrasting conclusions are multiple (see Gildersleeve, Haselton, & Fales, 2014b), but are not the focus here. Wood et al (2014) found certain groups of cycle effects to be robustspecifically, on preferences for symmetry and health, the effect for masculinity preferences just falling short of significance (see also Gildersleeve et al, 2014aGildersleeve et al, , 2014b. But they conclude, "The few instances in which women's preferences shifted across the cycle appeared to be largely artifacts of research practices" (p. 245).…”
mentioning
confidence: 99%
“…Other research has failed to find any link between preferences for facial masculinity and preferences for perceived health (Boothroyd et al, 2005;Enlow, Moyers, & Merow, 1982). Meanwhile, current evidence regarding women's preferences for masculine faces increasing closer to ovulation is equivocal, with two competing meta-analyses published in the same year reaching separate conclusions (Gildersleeve, Haselton, & Fales, 2014a, 2014bJones et al, 2017;W. Wood, Kressel, Joshi, & Louie, 2014).…”
Section: Inconsistencies In the Evolutionary Psychology Of Mating Strmentioning
confidence: 99%